Effects of Rainfall Seasonality on Scarabaeinae dung Beetles in an Agriculture Habitat in South Western Ghats - Latha, Thomas (International Journal of Environment, Agriculture and Biotechnology, 2019)
Scarabaeinae dung beetles are a ubiquitous group of beetles that are detritivores and provides important ecological services to the ecosystem. They are biological indicators and their community structure is affected by physical and biotic characteristics of the environment. Rainfall is an important parameter that affects these beetles. Rainfall seasonality of dung beetles in an agriculture habitat in South Western Ghats was studied. Cow dung baited pitfall traps were used to trap dung beetles in a banana plantation during the northeast monsoon, summer and southwest monsoon season. The study showed that agriculture activities affected dung beetle community attributes in the three seasons. Abundance, species richness and diversity was lowest in the northeast monsoon season characterized by moderate rainfall and ideal environmental conditions. This was a result of agricultural practices in the region, where banana cultivation activities peaks in the northeast monsoon season, which makes conditions unfavorable for dung beetles to colonize the agriculture habitat during this season.